1989
DOI: 10.1128/mcb.9.5.2279
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of a human mitochondrial protein homologous to the bacterial and plant chaperonins and to the 65-kilodalton mycobacterial antigen.

Abstract: The complete cDNA for a human mitochondrial protein designated P1, which was previously identified as a microtubule-related protein, has been cloned and sequenced. The deduced amino acid sequence of P1 shows strong homology (40 to 50% identical residues and an additional 20% conservative replacements) to the 65-kilodalton major antigen of mycobacteria, to the GroEL protein of Escherichia coli, and to the ribulose 1,5-bisphosphate carboxylase-oxygenase (rubisco) subunit binding protein of plant chloroplasts. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
230
0
6

Year Published

1990
1990
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(243 citation statements)
references
References 22 publications
7
230
0
6
Order By: Relevance
“…Mammalian Hsp60 proteins commonly share 40-50% amino acid sequence homology with Cpn60.2 (Jindal et al, 1989;Tasci et al, 1998). It has been shown that mammalian and bacterial homologues of Hsp60/65 bind to the MF at different sites (Habich et al, 2003) and the findings from our competitive inhibition assay (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Mammalian Hsp60 proteins commonly share 40-50% amino acid sequence homology with Cpn60.2 (Jindal et al, 1989;Tasci et al, 1998). It has been shown that mammalian and bacterial homologues of Hsp60/65 bind to the MF at different sites (Habich et al, 2003) and the findings from our competitive inhibition assay (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, eosinophilia in the lung tissue and airways was prevented after treatment with M. leprae hsp, but not with the other hsp. These findings imply that despite their enormous conservation in amino acid sequences (36), microbial hsp differ in their immunological properties.…”
Section: Discussionmentioning
confidence: 88%
“…(B cyt45011); rat ornithine carbamoyltransferase [36], (R oct); human pyruvate dehydrogenase EI~ subunit [37], (H PyrDhE1); bovine mitochondrial adenylate kinase 2 [38], (B AK2A, B AK2B); bovine mitochondrial carrier protein [39], (B mtPcP); rat mitochondrial 3-oxoacyl-CoA thiolase [40], (R 3oxCoth); human liver glutamate dehydrogenase [41], (H GDH); rat heart and liver subunit Via of cytochrome oxidase [42], (R hcoxVIa. R IcoxVla); mouse mitochondrial uncoupling protein [43], (M Ucp, M Ucp/min); mouse ornithine transcarbamylase [44], (Motc); mouse mitochondrial malate dehydrogenase [45], (M mMDH); human cytochrome oxidase subunit Vie [46], (H coxVIc); human aspartate amino transferase [47], (H mAspAT); rat liver mitochondrial NADH dehydrogenase 24-kDa subunit [67], (H cox-VIII); murine NAD-dependent methylenetetrahydrofolate dehydrogenase-melthylenyltetrahydrofolate cyclohydrolase [68], (M MTHFdeh); bovine GTP:AMP phosphotransferase [69], (B AK3); bovine NADH-ubiquinone reductase [70], (B ubiqred); human methylmalonyl-CoA mutase [71], (H Metmlmt); human mitochondrial protein homologous to the bacterial and plant chaperonms [72], (H PI); porcine testis cytochrome P-450 (SCC) [73], (P cytp450); human cytochrome oxidase subunit Vlb [74], (H coxVIb); human creatine kinase [7'5]. (H CK); rat fumarase [76], (R mtFumra); human branched chain ~-keto acid dehydrogenase complex subunit E1 ~ [77], (H E1 BCKD); rat brain and liver cytochrome oxidase subunit IV [78], (R coxlV); bovine uncoupling protein [79], (B Ucp); rat cytochrome c oxidase subunh Via (Vb) [80], (R coxVb); human cytochrome c oxidase subunit Via [81], (H coxVia); human NAD-dependent methylene tetrahydrofolate dehydrogenase-cyc!ohydrolase [82], (H MTHFdeh); rat short chain acyl-CoA dehydrogenase and isovaleryl-CoA dehydrogenase [83], (R SCCode, R IVD); mouse cytochrome oxidase subunit Ya [84], (M coxVa); human cytochrome bcl complex core protein 2 [85]; human cytOchrome c oxidase subunit VIIa …”
Section: Resultsmentioning
confidence: 99%